067 Food insecurity, well-being and inequalities in diet in UK women. (16th November 2010) - Baird, J; Lawrence, W; Jarman, M; Black, C; Inskip, H; Cooper, C; Barker, M; ,
Abstract : Objective: Prevalence of household food insecurity varies between populations, but is higher among those who have low incomes, poor educational attainment and low sense of well-being. The impact of household food insecurity on an individual's quality of diet depends on their role within the household and mothers may be more adversely affected than other family members. Studies have linked food insecurity with mental health problems in women of childbearing age. This study examines the relationship between food insecurity, well-being and quality of diet in women of childbearing age. Design: Cross-sectional survey of educational attainment, food insecurity, well-being and quality of diet in women of childbearing age. Setting: Sure Start Children's Centres (SSCCs) in three south coast towns with high levels of disadvantage- Southampton, Gosport and Havant. Participants: 1022 women attending SSCCs between January and April 2009. Main outcome measures: Food insecurity, assessed using the short form of Blumberg household food security scale; dietary quality score from a 20-item food frequency questionnaire; well-being by the WHO-5 questionnaire. Results: 11% of women had insufficient money to buy food, and 9% reported going hungry. Women of lower educational attainment were twice as likely to be food insecure as women of higher educational attainment (prevalence rate ratio 2.02, 95% CIs 1.42 to 2.86). Women who reported lower well-being were three times as likely to go hungry as women of higher well-being (prevalence rate ratio 3.18, 95% CIs 2.04 to 4.93.) Women who experienced food insecurity had poorer quality diets: becoming food insecure was accompanied by a 0.79 standard deviation reduction in dietary quality score (95% CIs −1.10 to −0.48). In a multivariate regression analysis, having lower educational attainment, lower well-being, being food insecure and going hungry were significant independent predictors of dietary quality, after adjusting for age and number of children in the household. Being food insecure predicted a 0.32 standard deviation reduction in dietary quality score (95% CIs −0.61 to −0.28), and going hungry a 0.45 standard deviation reduction (95% CIs −0.77 to −0.12). Conclusion: Food insecurity was common: one in five women lived in food insecure households. Women of lower educational attainment were twice as likely to be food insecure as women of higher educational attainment. National survey data indicate that disadvantaged young women have diets of poor quality. Our study suggests that food insecurity and low sense of well-being are aspects of disadvantage that predict poor quality of diet.